Answer:
(-3, -7).
Explanation:
1. Write the expressions.
![(1)y= 2x-1\\ \\ (2)y= 3x+2](https://img.qammunity.org/2023/formulas/mathematics/college/vqtnyiy9q8hxa2cn220rojx822e8q8bz79.png)
2. Write equation 1 and substitute its y value by the argument of expression 2.
![(3x+2)= 2x-1\\ \\3x+2= 2x-1](https://img.qammunity.org/2023/formulas/mathematics/college/hi5upxoqxlkkyd42513htrvf45s9yuz1wg.png)
3. Subtract 2 in both sides of the equation.
![3x+2-2= 2x-1-2\\ \\3x=2x-3](https://img.qammunity.org/2023/formulas/mathematics/college/i3fvvn6po1wlvprowt6yikgt9gfozypypw.png)
4. Subtract 2x from both sides of the equation.
![3x-2x=2x-3-2x\\ \\x=-3](https://img.qammunity.org/2023/formulas/mathematics/college/3uj5e8q53r8wrltjob7bch2q7lmcxqx0po.png)
5. Verify the answer.
To see of the answer is correct, both of the equation should give the same y value for the x value of -3.
![(1)y= 2(-3)-1\\ \\ y=-6-1\\ \\y=-7](https://img.qammunity.org/2023/formulas/mathematics/college/d0mx4bxxsu2y416igid2bj65azsy2b0be5.png)
![(2)y= 3(-3)+2\\ \\y=-9+2\\ \\y=-7](https://img.qammunity.org/2023/formulas/mathematics/college/kf6pes6dn0nmc0cyxad4sh04syhdtr1rs7.png)
6. Express the final result.
(x, y)
(-3, -7).